The Effect of Inflation, Interest Rates, IDR / USD Exchange Rates and Money Supply on The LQ45 Stock Price Index on The Indonesia Stock Exchange for The Period 2016 – 2020 - Munasir Munasir; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of Indonesian macroeconomic factors on the LQ45 stock index of the Indonesia Stock Exchange: inflation, interest rates, IDR/USD exchange rate, and the money supply. The survey period covers the period from 2016 to 2020. The subject of this research is the LQ45 stock index of the Indonesia Stock Exchange. The data used is secondary data. The data analysis method used is multiple regression analysis with a significance level of 0.05 or 5%. The results of this study show that inflation has a positive and insignificant effect on the LQ45 stock price index in 2016-2020. The results of the interest rate variable show that interest rates have a positive and insignificant effect on the 2016-2020 LQ45 stock price index. The results of the exchange rate variable (X3) show that the IDR/USD exchange rate has a negative and significant effect on the 2016-2020 LQ45 Stock Price Index. The results of the Amount of Money Supply (JUB) variable show that the Money Supply (JUB) has a positive and insignificant effect on the LQ45 stock price index 2016-2020.